2013
DOI: 10.3389/fpls.2013.00381
|View full text |Cite
|
Sign up to set email alerts
|

Heterochronic genes in plant evolution and development

Abstract: Evolution of morphology includes evolutionary shifts of developmental processes in space or in time. Heterochronic evolution is defined as a temporal shift. The concept of heterochrony has been very rewarding to investigators of both animal and plant developmental evolution, because it has strong explanatory power when trying to understand morphological diversity. While for animals, extensive literature on heterochrony developed along with the field of evolution of development, in plants the concept has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…For example, it is hypothesized that an extended phase of rapid brain growth (a characteristic of juvenile development) played a key role in the evolution of humans from their primate ancestors (Gould, 1977). In flowering plants, changes in the relative timing of juvenile and adult development can have major effects on traits such as leaf morphology and the onset of flowering (reviewed by Huijser and Schmid, 2011;Geuten and Coenen, 2013;Poethig, 2013). Resistance to herbivory, as well as changes in cell wall composition, also have an important temporal component (Abedon et al, 2006; reviewed by Boege andMarquis, 2005 andChandler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is hypothesized that an extended phase of rapid brain growth (a characteristic of juvenile development) played a key role in the evolution of humans from their primate ancestors (Gould, 1977). In flowering plants, changes in the relative timing of juvenile and adult development can have major effects on traits such as leaf morphology and the onset of flowering (reviewed by Huijser and Schmid, 2011;Geuten and Coenen, 2013;Poethig, 2013). Resistance to herbivory, as well as changes in cell wall composition, also have an important temporal component (Abedon et al, 2006; reviewed by Boege andMarquis, 2005 andChandler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that the h QTL functional mapping model can reveal more intricate details of environmental responses of dynamic traits such as leaf growth, or any other similar trait. These results also show the dynamic complexity of growth and developmental mechanisms plant can use for adaptation to different environments (Geuten & Coenen, 2013). Heterochrony genes control precisely timed switches for developmental transitions, and provide in this way a time dimension to developmental regulation (Moss, 2007;Geuten & Coenen, 2013).…”
Section: Researchmentioning
confidence: 81%
“…These results also show the dynamic complexity of growth and developmental mechanisms plant can use for adaptation to different environments (Geuten & Coenen, 2013). Heterochrony genes control precisely timed switches for developmental transitions, and provide in this way a time dimension to developmental regulation (Moss, 2007;Geuten & Coenen, 2013). Some heterochrony genes may possess homologs in other species.…”
Section: Researchmentioning
confidence: 82%
“…When miR156 levels decline, the level of SPL proteins increases, miR172 is activated, fl owering genes are activated, and adult leaf features are induced. When miR172 levels are increasing, the APETALA2-like ( AP2-like ) genes are progressively silenced and adult leaf traits as well as fl owering are induced (see in Geuten and Coenen 2013 ). More miRNAs are being described as important players in plant development as expected from their early evolution (Fig.…”
Section: Homeobox Genes and Body Developmentmentioning
confidence: 99%
“…The total number of Hox genes found among plant genomes refl ects the complex patterns of genome duplication and gene duplication or loss that have characterized the evolutionary histories of these species and the higher developmental and organizational complexity in angiosperms than in mosses and unicellular algae (Mukherjee et al 2009 ). In contrast to animals, plants entail the continuous development of new organs as time progresses (Geuten and Coenen 2013 ) (Friedman et al 2004 ). (v) Flowers .…”
Section: Homeobox Genes and Body Developmentmentioning
confidence: 99%